2022
DOI: 10.3390/antibiotics11030415
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Fluoroquinolones and Other Antibiotic Prophylaxis Regimens for Preventing Complications in Patients Undergoing Transrectal Prostate Biopsy

Abstract: Our study aimed to compare the incidence of infective complications after transrectal ultrasound-guided prostate biopsy (TRUSBx) when adopting different antimicrobial prophylaxis regimens. A multi-institutional cohort of 1150 patients who underwent TRUSBx was retrospectively analyzed. Procedures were performed between 2017 and 2019 (before and after the EMA warning about the use of fluoroquinolones for the antibiotic prophylaxis of patient candidates to TRUSBx). The primary endpoint was the occurrence of infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Although several studies examining the effectiveness of FM compared with FQ showed that the use of FM alone would be an attractive alternative to FQ as prophylaxis for TRUSPB [ 11 12 13 14 ], this was not the case in the Republic of Korea. However, a combination of FM and FQ was observed to be effective in reducing post-biopsy infections [ 9 ], which may be attributed to regional differences in the antibiotic resistance pattern [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several studies examining the effectiveness of FM compared with FQ showed that the use of FM alone would be an attractive alternative to FQ as prophylaxis for TRUSPB [ 11 12 13 14 ], this was not the case in the Republic of Korea. However, a combination of FM and FQ was observed to be effective in reducing post-biopsy infections [ 9 ], which may be attributed to regional differences in the antibiotic resistance pattern [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…With increasing antibiotic-resistant bacterial infections, particularly high fluoroquinolone (FQ) resistance in the Republic of Korea [ 5 6 ], alternative antimicrobial prophylaxis is required to prevent post-TRUSPB-related infections. Owing to its good permeability into prostate tissue and lower resistance rate [ 7 ], FM trometamol has emerged as an alternative to FQ for the prophylaxis of post-biopsy infectious complications.…”
Section: Introductionmentioning
confidence: 99%
“…Desde la descripción original de Nash en 1996, el estándar para la biopsia prostática es el uso de anestesia local para bloqueo periprostático, disminuyendo considerablemente el dolor 5 . Por otro lado, para disminuir las complicaciones infecciosas, el uso de povidona yodada rectal antes de la biopsia y la administración de profilaxis antimicrobiana han demostrado ser efectivos en la prevención de complicaciones infecciosas, pero no existe evidencia de que un esquema de antibióticos sea mejor que otro 6 . También se ha introducido el uso de enema rectal evacuante previo al procedimiento, aunque no hay trabajos que lo recomienden fuertemente.…”
Section: Introductionunclassified
“…Furthermore, TRUS seems no more accurate than DRE at predicting organ-confined PCa [6]. However, real-time ultrasound (US) guidance remains critical for performing both systematic and fusion prostate biopsies [7][8][9]. As part of the new imaging exams, prostate-specific membrane antigen positron emission tomography/CT (PSMA PET/CT) has gained great popularity in recent years.…”
Section: Introductionmentioning
confidence: 99%